Improving the Availability and Management of Essential AIDS and TB Medicines and Diagnostics in Uganda - HEPS-Uganda (HEPS-Uganda, 2008)
A free ARV programme implemented with support from external donors has over the past few years led to a significant increase in the number of people living with HIV/AIDS (PHAs) accessing antiretroviral therapy (ART). By 2006/7, about 105,000 PHAs were receiving ART from 313 centres. Given the relatively wide range of ARVs available for prescription to PHAs, Uganda is well into the modern trends of AIDS treatment. The substantial availability of combination ARVs brings with it the advantages of a reduced pill burden and thus, improved adherence. In addition, the availability levels of medicines at treatment centres located in rural areas is comparable to those in urban locations, suggesting the medicine distribution system is generally fair. These advances in the treatment effort however, mask the reality, extent and impact of stock-outs of the essential AIDS ad TB medicines in the accredited centres. Access to affordable medicines is a human right enshrined in the UN Universal Declaration on Human Rights, which together with subsequent UN statements, affirms people’s right to health. The reliable provision of ART to at least the people who are registered to receive it is therefore a key component of an adequate, functioning health care system that enables people to realise their right to health. As government plans to roll out ART to 80% of Health Centre IV’s by 2010, it is important to consider whether the present PHAs on ART can access treatment at the accredited health facilities. Besides risking their lives, if treatment of PHAs is interrupted for one reason or another, they are likely to develop resistance to the medicines they are currently taking, which could lead to emergence of resistant strains of HIV among the general society if any of the affected PHAs transmits HIV to other people.